Changes in pulmonary artery size before and after total cavopulmonary connection. Issue 5 (1st November 1997) - Buheitel, Gernot; Hofbeck, Michael; Tenbrink, Ursula; Leipold, Georg; von der Emde, Jürgen; Singer, Helmut
Abstract : Objective —To assess changes in size of the central pulmonary arteries following a total cavopulmonary connection (TCPC). Design: A retrospective analysis of the angiographic diameters of the central pulmonary arteries, expressed as z scores, in infancy before the TCPC and 3.5 (0.9) years (mean (SD)) later. Analysis of the relation between the pulmonary arteriolar resistance and the z scores at follow up. Setting: Tertiary referral centre. Patients: 32 patients who had TCPC from February 1990 to July 1993. Results: The patients were divided into two groups (n = 16) depending on their preoperative flow ratio: group I, Qp/Qs ⩽ 1; group II, Qp/Qs > 1. At the initial study in infancy the mean z scores in group I were −6.0 for the right pulmonary artery (RPA) and −9.6 for the left pulmonary artery (LPA); in group II the respective values were −2.7 and −3.0. Before the TCPC the values increased to 0.5 (RPA) and −0.5 (LPA) in group I, and to 8.8 (RPA) and 8.2 (LPA) in group II. At follow up the z scores decreased to −2.4 (RPA) and −4.9 (LPA) in group I, and to 2.2 (RPA) and −0.7 (LPA) in group II. The changes in pulmonary artery diameters were significant for both groups (p < 0.02). Following the TCPC, no significant difference in pulmonary arteriolar resistance index was found between patients with relatively small pulmonary arteries (z score RPA+LPA ⩽ 0) and those with relatively large pulmonary arteries (z score RPA+LPA > 0). Conclusions: Creation of a TCPC results in a significant reduction in size of the central pulmonary arteries. At a mean interval of 3.5 years following the TCPC, however, there was no significant difference in pulmonary arteriolar resistance index between patients with smaller and larger central pulmonary arteries.